Konflik Politik dan Lingkungan : Studi Tentang Pembangunan PLTU Ropa Kecamatan Maurole Kabupaten Ende - Agustinus Salman Sidi; Ananias R. P. Jacob; Ambrosius Dedi A. Sinu; Rex Tiran (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study aims to analyze the dynamics of political and environmental conflicts in the development of the Ropa Coal-Fired Power Plant (PLTU Ropa) in Maurole District, Ende Regency, and to identify the factors influencing conflicts among the local community, the government, and the company. Although the construction of PLTU Ropa was intended to support electricity supply and regional development, its implementation has generated various social, political, and environmental issues that have led to prolonged conflicts within the community. This research employed a qualitative approach using a descriptive research design. Data were collected through interviews, observations, and documentation, and were analyzed using Ralf Dahrendorf's Conflict Theory, which emphasizes unequal distribution of power and authority as the primary source of social conflict. The findings indicate that the conflict originated from two major issues, namely land acquisition and environmental impacts resulting from the plant's operation. Political conflict emerged due to the community's dissatisfaction with the land acquisition process, which was perceived as lacking transparency, public participation, and fairness in compensation. Environmental conflict was driven by air pollution caused by coal dust and fly ash, which affected environmental quality, agricultural productivity, fisheries, and public health. The factors influencing the conflict include unequal power relations, weak communication and transparency, limited community participation in decision-making, and differing interests between economic development and environmental protection. The study concludes that resolving the conflict requires strengthening dialogue among stakeholders, improving transparency, and enhancing public participation to achieve a more equitable, inclusive, and sustainable development process.